2011
DOI: 10.1001/archsurg.2011.725
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis Before Surgery vs After Cord Clamping in Elective Cesarean Delivery

Abstract: Perioperative antibiotic prophylaxis during elective cesarean delivery at term to reduce postoperative maternal infectious morbidity is generally used but may not be effective on the basis of the available data. Also, the optimal timing of prophylactic antibiotic administration is unclear.Objective: To compare the effectiveness of cefazolin administered before skin incision vs cefazolin administered after umbilical cord clamping vs placebo in a 3-arm randomized trial. The primary objective of the study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 19 publications
(30 reference statements)
0
49
2
1
Order By: Relevance
“…No new trials were identified by reference search. In total, 6 randomized controlled trials comparing prophylactic cefazolin for cesarean delivery given before the procedure versus at cord clamping were included in this meta-analysis [12,13,14,15,16,17]. In the 6 randomized controlled trials, 1,168 women received cefazolin preoperatively, and 1,167 women received it after cord clamping.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No new trials were identified by reference search. In total, 6 randomized controlled trials comparing prophylactic cefazolin for cesarean delivery given before the procedure versus at cord clamping were included in this meta-analysis [12,13,14,15,16,17]. In the 6 randomized controlled trials, 1,168 women received cefazolin preoperatively, and 1,167 women received it after cord clamping.…”
Section: Resultsmentioning
confidence: 99%
“…However, more and more studies have been performed to determine whether the administration of cefazolin prior to skin incision is superior to administration at the time of umbilical cord clamping for the prevention of postcesarean infectious morbidity [10,11,12,13,14,15,16,17]. The aim of our work was to summarize the evidence of prophylactic cefazolin for cesarean delivery given before the procedure versus at cord clamping.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of the meta-analysis by Costantine et al, 16 two other randomized controlled trials addressing the timing of antibiotic administration at cesarean, have been published. 13,14 Both these studies did not find a significant difference in infection rate between the groups.…”
Section: Discussionmentioning
confidence: 83%
“…The debate on the timing of antibiotic administration at cesarean has emerged in the last several years with the publication of several observational studies, 6,9,11 clinical trials, 5,7,8,10,[12][13][14]18 a review article, 19 and meta-analyses. 16,20 These results culminated in American College of Obstetricians Gynecologists issuing a Committee Opinion advocating that all women undergoing a cesarean delivery be given prophylactic antibiotics before skin incision, 17 and the National Institute for Health and Clinical Excellence advising clinicians to offer prophylactic antibiotics at cesarean before skin incision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation